2006
DOI: 10.1007/s00232-005-0834-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-electrical Transduction: New Insights into Old Ideas

Abstract: The gating-spring theory of hair cell mechanotransduction channel activation was first postulated over twenty years ago. The basic tenets of this hypothesis have been reaffirmed in hair cells from both auditory and vestibular systems and across species. In fact, the basic findings have been reproduced in every hair cell type tested. A great deal of information regarding the structural, mechanical, molecular and biophysical properties of the sensory hair bundle and the mechanotransducer channel has accumulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 131 publications
(204 reference statements)
1
41
0
Order By: Relevance
“…Further, the instantaneous current is detected at high extracellular K ϩ (25), as would be present extracellularly in endolymph. Interestingly, structural investigations have suggested that the hair cell mechanosensory transduction channels "may be located only on the tops of the shorter stereocilia" (42,43), and it is the tops of shorter stereocilia that appear to represent the site of protocadherin 15 (CD3) localization, as opposed to cadherin 23, the other putative component of tip links with stereociliary insertion points localized midway along the taller stereocilia (8). Further, recent experiments point to the tips of the shorter stereocilia as sites for calcium entry, required in the adaptation phase of mechanosensory transduction, again consistent with colocalization of mechanosensory transduction channels and protocadherin 15 tip link insertion sites (44 -46).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the instantaneous current is detected at high extracellular K ϩ (25), as would be present extracellularly in endolymph. Interestingly, structural investigations have suggested that the hair cell mechanosensory transduction channels "may be located only on the tops of the shorter stereocilia" (42,43), and it is the tops of shorter stereocilia that appear to represent the site of protocadherin 15 (CD3) localization, as opposed to cadherin 23, the other putative component of tip links with stereociliary insertion points localized midway along the taller stereocilia (8). Further, recent experiments point to the tips of the shorter stereocilia as sites for calcium entry, required in the adaptation phase of mechanosensory transduction, again consistent with colocalization of mechanosensory transduction channels and protocadherin 15 tip link insertion sites (44 -46).…”
Section: Discussionmentioning
confidence: 99%
“…While several mechanosensory units are membrane based proteins, nevertheless several such proteins belong to the soluble repertoire as well (Vogel, 2006;Vogel and Sheetz, 2006). Loss or aberrant mechanosensing and transduction of mechansensory signal may also be part of pathology in progressive hearing loss (Knoll et al, 2003;Ricci et al, 2006). Dysfunction or absence of any of the mechanosensing transmembrane molecules results in disruption of the network causing sensorineural degeneration in the inner ear and in the retina in Usher syndrome, another disease that leads to retinal degeneration and progressive hearing loss (Reiners et al, 2006), and other forms of progressive hearing losses such as DFNA4 and DFNB6 (Bearer et al, 2000;Mitchem et al, 2002).…”
Section: Cochlin and Extracellular Matrixmentioning
confidence: 99%
“…Many types of cells are reported to sense mechanical stimulation, which are transformed into intracellular signals [22,23]. With respect to regulators of cellular mechanical properties, Ca 2+ influx, integrin complex activation, and RhoA activation are known to act as first messengers [24].…”
Section: Resultsmentioning
confidence: 99%